Pembangunan Sistem Manajemen Data Wisata pada Dinas Pariwisata, Pemuda, dan Olahraga Kabupaten Madiun - Yusuf Fadlila Rachman; Trisna Ari Roshinta; Darmawan Lahru Riatma; Masbahah Masbahah; Nur Azizul Haqimi (ALKHIDMAH: Jurnal Pengabdian dan Kemitraan Masyarakat, 2024)
The tourism sector in Madiun Regency has significant development potential, highlighted by 75 tourist destinations. However, inadequate management of tourism data has led to suboptimal growth. To address this issue, a tourism data management system is proposed to facilitate efficient data handling for various stakeholders, including Destination Managers, Tourism Industry Managers, and Service Verifiers. The system manages data on tourist destinations, the tourism industry, and visitor information. The results of system testing using the black box method show that all features are functioning properly. The system was tested using usability testing, it showed a score of 87% from a total of 53 respondents, indicate that the developed system is both functional and user-friendly.